2022
DOI: 10.3390/app12062858
|View full text |Cite
|
Sign up to set email alerts
|

Passive Thermal Control Design Methods, Analysis, Comparison, and Evaluation for Micro and Nanosatellites Carrying Infrared Imager

Abstract: Advancements in satellite technologies are increasing the power density of electronics and payloads. When the power consumption increases within a limited volume, waste heat generation also increases and this necessitates a proper and efficient thermal management system. Mostly, micro and nanosatellites use passive thermal control methods because of the low cost, no additional power requirement, ease of implementation, and better thermal performance. Passive methods lack the ability to meet certain thermal req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Therefore, it is concluded that after the usage of the thermal strap, all the electronic components do not exceed the operational limit. S. Selvadurai et al [9] have listed viable passive thermal control design methods for nanosatellites and discussed about thermal straps and multi-layer insulation. in this study a detailed transient thermal analysis is performed on the two potential passive thermal control methods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is concluded that after the usage of the thermal strap, all the electronic components do not exceed the operational limit. S. Selvadurai et al [9] have listed viable passive thermal control design methods for nanosatellites and discussed about thermal straps and multi-layer insulation. in this study a detailed transient thermal analysis is performed on the two potential passive thermal control methods.…”
Section: Resultsmentioning
confidence: 99%
“…the lightweight nature of aerogel makes it perfect for use with extremely delicate and fragile components. thermal strap is selected as the CubeSat's insulation because it is available in a variety of shapes and lengths based on the demand [9]. thermal straps are well suited for small scale satellites.…”
Section: Thermal Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Attitude Z-axis to ground orientation The input parameters bearing uncertainties, as identified for the purposes of this investigation [10], alongside their average values, are elucidated in table 3. The input parameters are normally distributed and their standard deviation is 0.05.…”
Section: Parameters Numerical Valuementioning
confidence: 99%
“…Since the external heat flux inside the satellite body is zero, the satellite body's reverse surface element is not considered in this study. The uncertainty input parameters selected for this study [29] and their average values are presented in Table 2. The input parameters are normally distributed and their standard deviation is 0.05.…”
Section: Experimental Modelmentioning
confidence: 99%